Chemical vapor deposition growth and characterization of graphite-like film. (13th January 2020) - Zhang, Yanhui; Shu, Haibo; Chen, Zhiying; Mu, Gang; Sui, Yanping; Liang, Yijian; Hu, Shike; Li, Jing; Kang, He; Yu, Guanghui; Peng, Songang; Jin, Zhi; et al.
Abstract: Thick graphene film can be widely used in surface protection, heat dissipation, heating devices and other fields. Here we present a study on the growth and characterization of large area continuous and patterned graphite-like films prepared on Ni foil through CVD. Effects of parameters on the material growth are studied experimentally and theoretically in detail. Thickness of the graphite-like film in this work can reach 500 nm and can be regulated by growth process. Characterization results show that the graphite-like film is formed by free stacking of large area graphene continuous films and possesses strong mechanical strength, chemical stability, good electrical conductivity and flexibility. The graphite-like film shows potential for application in metal surface protection, flexible conduction, heating and electromagnetic shielding.